Existence result for a dislocation based model of single crystal gradient plasticity with isotropic or linear kinematic hardening. Issue 1 (9th December 2017) - Ebobisse, François; Neff, Patrizio; Aifantis, Elias C
Summary: We consider a dislocation-based rate-independent model of single crystal gradient plasticity with isotropic or linear kinematic hardening. The model is weakly formulated through the so-called primal form of the flow rule as a variational inequality for which a result of existence and uniqueness is obtained using the functional analytical framework developed by Han-Reddy.